Synthesis, Spectral, and Biological Properties of Copper(II) Complexes of Thiosemicarbazones of Schiff Bases Derived from 4-Aminoantipyrine and Aromatic Aldehydes - Ram K. Agarwal; Lakshman Singh; Deepak Kumar Sharma (Bioinorganic Chemistry and Applications)
We have synthesized a novel series of Schiff bases by condensation of 4-aminoantipyrine and various aromatic aldehydes followed by reaction with thiosemicarbazide. These thiosemicarbazones are potential ligands toward transition metal ions. The reaction of copper(II) salts with 4[N-(benzalidene)amino]antipyrinethiosemicarbazone (BAAPTS), 4[N-(4′-methoxybenzalidene) amino] antipyrinethiosemicarbozone (MBAAPTS), 4[N-(4′-dimethylamino benzalidene) amino] antipyrinethiosemicarbazone (DABAAPTS), and 4[N-(cinnamalidene) amino] antipyrinethiosemicarbazone (CAAPTS) resulted in the formation of solid complexes with the general composition CuX2⋅(H2O)(L)(X = Cl, Br, NO3, NCS, or CH3COO; L = BAAPTS, MBAAPTS, DABAAPTS, or CAAPTS). These complexes were characterized through elemental analysis, molecular weight, electrical conductance, infrared, electronic spectra, and magnetic susceptibilities at room temperature. Copper(II) complexes with BAAPTS and MBAAPTS were screened for antibacterial and antifungal properties and have exhibited potential activity. Thermal stabilities of two representative complexes were also investigated.